Graphene Nanobubbles: A New Optical Nonlinear Material. Issue 6 (2nd February 2015) - Bao, Qiaoliang; Chen, Jianqiang; Xiang, Yuanjiang; Zhang, Kai; Li, Shaojuan; Jiang, Xiaofang; Xu, Qing‐Hua; Loh, Kian Ping; Venkatesan, T.
<x xml:space="preserve">Abstract</x> All‐optical switching in graphene nanobubbles is demonstrated in this work. Thermally stressing graphene to form an array of nanobubbles allows a large optical phase shift to be obtained due to their vertical side walls and added curvature. Graphene nanobubbles offer a new and promising type of optical nonlinear medium to overcome the optical path length limitation of atomically thin two‐dimensional films, and enable exploration of such elements as the building blocks of digital all‐optical circuitry.